Analysis of Symbolic Power in the Indonesia–China High-Speed Rail Development Policy (KCIC/Whoosh): Analisis Kekuasaan Simbolik dalam Kebijakan Pembangunan Kereta Cepat Indonesia China (KCIC/ Whoosh) - Zainul Abidin; Michael Mamentu; Johny Peter Lengkong (Jurnal Pemerintahan dan Politik, 2026)
Purpose : This study aims to analyze how China’s symbolic power, manifested through the accumulation of economic modalities in the form of money or financial capital, and Jokowi’s symbolic power, manifested through the accumulation of symbolic modalities such as authority and prestige as the President of Indonesia, operate within the development of the KCIC. Design : This study employs a qualitative method in the form of library research, using a content or thematic analysis approach. Findings : The findings of this study reveal the following. First, China, through the KCIC/Whoosh policy, constructs symbolic power in the form of efforts to dominate influence in Indonesia, driven by its ambition to advance the Belt and Road Initiative (BRI). Second, Jokowi builds symbolic power in the form of a legacy of transportation infrastructure modernization. Although both China and Jokowi are able to construct symbolic power within the KCIC project, this power tends to be fragile. The fragility arises because KCIC has not yet been fully accumulated as a new symbolic modality. Practical Implication : These include recommendations to conduct a reassessment of the interest burden, to integrate the high-speed rail with efficient local transportation so that this symbolic power is not perceived as fragile, and for the government to exercise greater caution in granting concessions over vital infrastructure while safeguarding strategic assets. Originality/value : This study theoretically complements Bourdieu by positioning its research findings within the framework of symbolic power.